Intersex Narratives Shifts in the Representation of Intersex Lives in North American Literature and Popular Culture - Amato, Viola (Queer Studies, 2016)
This book explores representations of intersex - intersex persons, intersex communities, and intersex as a cultural concept and knowledge category - in contemporary North American literature and popular culture. The study turns its attention to the significant paradigm shift in the narratives on intersex that occurred within early 1990s intersex activism in response to biopolitical regulations of intersex bodies. Focusing on the emergence of recent autobiographical stories and cultural productions like novels and TV series centering around intersex, Viola Amato provides a first systematic analysis of an activism-triggered resignification of intersex.